Desain Badan Peradilan Khusus Pemilihan Kepala Daerah dalam Rangka Menghadapi Pemilihan Kepala Daerah Serentak Nasional Tahun 2024 - Ispan Diar Fauzi (Badan Pengawas Pemilihan Umum, 2018)
This study aims to answer the problems, the formulation and design of the special courts election and the excellences of the special courts election. This was conducted using legal-normative research through conceptual approach. In this study, special court local election are designed as a permanent adjudication court. The judicial jurisdiction under the Supreme Court includes the High Court for the special court of election of the Governor and the District Court for the special court of election of the Regent / Mayor. Special court designed has three assemblies, state administrative dispute assemblies, criminal act assemblies and dispute of electoral results assemblies. The authority of the special court election is to examine and decide all disputes during the election process. For the composition of the judges will be filled by career judges and ad hoc judges. Special court electoral in each jurisdiction are designed as the first and final judicial institutions whose decisions are final and binding. One of the advantage of special court election is the special court of local elections which provides for the settle of all disputes during the election process.